Perkembangan Tindak Pidana Pencucian Uang (Money Laundering) Dan Dampaknya Terhadap Sektor Ekonomi Dan Bisnis - Iwan Kurniawan (Jurnal Ilmu Hukum, 2013)
Money laundering is the process by which one conceals the existence, illegal source, or illegal application of income, and then disguises that income to make it appear legitimate. Money laundering has been known since the 18th century. However, this action was criminalized in 1980 with the adoption of the anti-money Laundering Act Central. (1986), which was later followed by The D'annunzio Wylie Act. and Money Laundering Suppression Act. (1994) by the United States Government. Whereas the Government of the Republic of Indonesia criminalized this action in 2002 by issuing Law Number 15 of 2002 On criminal offence of money laundering. The crime of money laundering has been giving a negative effect on the economy and business fields i.e., undermines legitimate private business sector, undermining the integrity of the financial markets, resulting in loss of control of the Government against its economic policy, and the onset of distortion and economic instability.